Experimental Study on SSRC under Eccentric Compression - Qingfu Li; Tianjing Zhang; Yaqian Yan; Qunhua Xiang (Advances in Civil Engineering)
The use of stainless steel bars can improve the durability and sustainability of building materials. Through the static performance test, this research analyzes the failure pattern and bearing performance of bias stainless steel reinforced concrete (SSRC) column. The influence of reinforcement ratio of longitudinal bars and eccentricity on the mechanical performance of specimens was studied. Different constitutive models of stainless steel bars were used to calculate the ultimate bearing capacity of the section of the column under eccentric compression column. Based on the experimental results, a method to modify the expression of the design specification is proposed. And, the results were compared with the test results. The results showed that the damage patterns and failure modes of SSRC columns are essentially the same as those of traditional reinforced concrete columns. The bearing capacity of SSRC columns rises with the increase in the longitudinal reinforcement ratio, and the ductility of the specimens is enhanced. The ultimate load of the specimen decreases with the rise in eccentricity but the deflection increases gradually. The strain distribution of the mid-span section of the SSRC column conforms to the plane section assumption. The bearing capacity of the specimen can be analyzed by referring to the calculation method of the specification, and some parameters in the calculation formula of the specification are modified to adapt to the design and calculation of the SSRC column.